Prescription of anorectic and benzodiazepine drugs through notification B prescriptions in Natal, Rio Grande do Norte, Brazil - Solange Aparecida Nappo; Elisaldo Araújo Carlini; Maria Dalva Araújo; Lúcio Flávio Sousa Moreira (Universidade de São Paulo, 2010)
A study was conducted on 22,158 special B prescriptions (notificações B) containing amphetamine-type anorectic drugs or benzodiazepines, obtained from compounding pharmacies or drugstores located in the city of Natal, RN, Brazil. The data obtained were compared with those from other Brazilian cities. Results showed that compounding pharmacies dispensed 85.4% of the prescriptions, indicating that these pharmacies filled out nearly 10 times more of these prescriptions than did the drugstores. The majority (83.5%) of B prescriptions issued for the compounding pharmacies were for women, where the female/male patient ratio ranged from 7.1/1.0 for mazindol to 10.3/1.0 for amfepramone. Similar results were obtained for the benzodiazepines with ratios of 1.9/1.0 for clonazepam to 15.6/1.0 for oxazepam. Omissions and mistakes were present in the B prescriptions, including missing information about the patient (in 49.6% of the documents) or about the pharmacies or drugstores (50.4%). There were cases where the name and/or CRM of the physician was lacking. It was noted that one medical doctor made out 1855 B prescriptions within one year. The same patient's name appeared on 138 prescriptions, and the same RG (identification card number) was present in 125 others. Comparison of Natal's data with those of several other Brazilian cities disclosed a striking similarity throughout Brazil, from Pelotas - Rio Grande do Sul State to Belem-Para State, revealing a practically identical medical/pharmaceutical behavior. This pattern of prescription/dispensation of amphetamine-type substances mostly to women for weight loss is therefore for cosmetic reasons. Consequently, there is an urgent need for an ethical review of this behavior. Foram examinadas 22.158 notificações B contendo substâncias anoréticas tipo-anfetamina ou de benzodiazepínicos, obtidas de drogarias e de farmácias de manipulação. Os dados foram comparados com os de outras cidades do Brasil, obtendo-se uma visão nacional sobre o assunto. Os achados mostraram que as farmácias de manipulação, dispensaram 85,4% das notificações, ou seja, as farmácias de manipulação atenderam cerca de 10 vezes mais do que as drogarias. A maioria (83,5%) das notificações B nas farmácias de manipulação eram destinadas às mulheres sendo a relação entre pacientes femininos/masculinos de 7,1/1,0 no caso do mazindol e de 10,3/1,0 para a anfepramona. Dados semelhantes foram obtidos para os benzodiazepínicos: relação de 1,9/1,0 para o clonazepam até 15,6/1,0 para o oxazepam. Falhas e erros gritantes foram também observados no preenchimento das notificações B: ausência de dados de pacientes (em 49,6% dos documentos), do fornecedor (50,4%) etc. Houve casos de notificações sem o nome ou CRM do médico e um único médico prescreveu 1.855 notificações B; o nome de uma mesma compradora apareceu em 138 notificações e um mesmo RG em 125 outras. A comparação destes achados com os de outras cidades mostrou uma surpreendente semelhança, ao longo do país, desde Pelotas-RS até Belém-PA; evidenciando um padrão de comportamento médico/farmacêutico praticamente idêntico. Este padrão de prescrição para mulheres destina-se mais para uma finalidade cosmética (perda de peso) do que para uma real necessidade terapêutica. É necessária uma revisão ética sobre este problema, que também tem sido observado e igualmente criticado em vários países.